2003
DOI: 10.32398/cjhp.v1i4.541
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Medicine Attitudes and Practices of U.S. College Students

Abstract: This study determined attitudes and practices, including gender differences, of college students regarding advocacy and use of alternative medicine. A convenience sample of students enrolled in undergraduate health classes from universities in five separate regions of the United States was surveyed using a written questionnaire. A total of 561 undergraduate and graduate students volunteered for this study. Results of this survey indicated that the majority of college students favor the use of alternative medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…Thus, familiarity and prior CAM use may predict willingness to use CAM again. Although few of our respondents came to the SHC for chronic pain, all of those who did were willing to use or consider CAM as a treatment option, consistent with a previous survey study that revealed that students with chronic illnesses were more likely to use CAM [5]. The National Health Interview Surveys (NHIS) has documented the rising use of CAM in the United States over the last decade, thus highlighting the importance of CAM education [3,4].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Thus, familiarity and prior CAM use may predict willingness to use CAM again. Although few of our respondents came to the SHC for chronic pain, all of those who did were willing to use or consider CAM as a treatment option, consistent with a previous survey study that revealed that students with chronic illnesses were more likely to use CAM [5]. The National Health Interview Surveys (NHIS) has documented the rising use of CAM in the United States over the last decade, thus highlighting the importance of CAM education [3,4].…”
Section: Discussionsupporting
confidence: 79%
“…Second, as young adults, college students are inclined to obtain health-related information from media forms like the Internet and may have more exposure to CAM advertisements [13]. Use of CAM modalities like vitamin/mineral supplements, herbal medicine, and massage is not unique to college students; the general population uses similar therapies [2,5,6,12]. However, college students have unique reasons for CAM use compared to those of the general adult population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A summary of findings regarding data sources and study details is provided in Table 2. 14-23 Published between 1999-2011, three of the 10 studies were published in the American Journal of Health Education, 17,21,22 two were found in the Journal of American College Health, 15,20 and the remaining five articles were published in the Journal of Hospital Marketing, 14 the Journal of the American Dietetics Association, 16 the Californian Journal of Health Promotion, 18 the Journal of the American Academy of Nurse Practitioners, 19 and Psychology, Health and Medicine. 23 Whereas one study collected data in five unidentified geographical regions of the U.S., 18 nine studies were conducted on a single campus or within a single school system.…”
Section: Resultsmentioning
confidence: 99%